1995
DOI: 10.1902/jop.1995.66.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Carbon Dioxide Laser in Retarding Epithelial Migration: A Pilot Histological Human Study Utilizing Case Reports

Abstract: Predictable regeneration of tooth-supporting tissues lost to periodontal disease is the aim of periodontal therapy. Often the result of conventional treatment is healing with a long junctional epithelium along the root surface and little regeneration of the complete attachment apparatus. The purpose of this pilot study was to evaluate whether de-epithelialization with a CO2 laser at the time of flap surgery and at 10-day intervals over the first 30 days of healing has the potential to enhance the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…In the treatment of inflammatory periodontal diseases, lasers may contribute to the bacterial reduction in periodontal pockets as well as to the removal of calculus and granulation tissue and can be used for contouring hyperplastic gingiva. An interesting aspect of laser application is the possibility of flap de-epithelization resulting in a retarded epithelial migration and an increased connective tissue formation [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of inflammatory periodontal diseases, lasers may contribute to the bacterial reduction in periodontal pockets as well as to the removal of calculus and granulation tissue and can be used for contouring hyperplastic gingiva. An interesting aspect of laser application is the possibility of flap de-epithelization resulting in a retarded epithelial migration and an increased connective tissue formation [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Clinical studies demonstrated a high supportive effect of many laser systems (Nd:YAG, Er:YAG, argon, CO 2 , and diode laser) when used in combination with scaling and root planing. [14][15][16][17][18][19][20] Several in vitro studies, however, indicated that lasers may severely damage root surface structures and inhibit new cellular attachment when certain energy levels are exceeded. [21][22][23][24][25][26] Moreover, the influence of pocket irradiation on collateral structures (gingiva, periodontal ligament, and alveolar bone) require considerable scientific investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Various animal and human studies demonstrate that a laser has the ability to retard the epithelial downgrowth and obtain new clinical attachment with bone fill in previously diseased sites. [45]…”
Section: Discussionmentioning
confidence: 99%